Creating Transdisciplinary Teaching Spaces. Cooperation of Universities and Non-University Partners to Design Higher Education for Regional Sustainable Transition - Hoinle, Birgit; Roose, Ilka; Shekhar, Himanshu (Sustainability, 2021)
Teaching formats involving non-university partners are increasingly gaining importance to deliver key competencies needed in higher education for sustainable development. Such teaching formats may also create new transdisciplinary spaces that allow different actors to impact regional transition towards sustainable development. Against this background, this article focuses on how universities foster regional transition through teaching, particularly in collaboration with local non-university. Using the interdisciplinary certificate programs on sustainable development offered by the German Universities of Tübingen and Duisburg-Essen as case studies, we analyze the potentials and challenges of teaching programs on sustainable development for promoting regional transition. Leaning on the multi-level-perspective-approach, we have used qualitative interviews to shed light on the design of cooperation between the university and regional partners as well as the creation and integration of transdisciplinary learning spaces. This paper shows that the impact of such teaching formats on the regional transition consists primarily of awareness and network building. One of the most fundamental challenges faced is unequal power relations in terms of access to resources, financing, and doing the course planning. Simultaneously, co-design, mutual understanding, and collective decisions on roles and responsibilities and—especially—empathy and trust are crucial factors for successfully teaching cooperation towards regional sustainability.